2020
DOI: 10.1089/cap.2019.0147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Discontinuing Methylphenidate on Strengths and Difficulties, Quality of Life and Parenting Stress

Abstract: Objectives: To study the effects of discontinuation of long-term methylphenidate use on secondary outcome measures of strengths and difficulties, quality of life (QoL), and parenting stress. Methods: Ninety-four children and adolescents aged 8 to 18 years who had used methylphenidate for over 2 years were randomly assigned to double-blind continuation of treatment for 7 weeks (36 or 54 mg extended release methylphenidate) or to gradual withdrawal over 3 to 4 weeks placebo. We used mixed models for repeated mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…The difference between the mean SDQ hyperactivity/inattention ratings in MPH periods and placebo periods was used as a summary measure for the treatment effect in an individual subject. The estimated standard deviation (SD) of 2.3 points for single ratings was used based on a reported standard error for the parent-rated SDQ subscale [42]. Using a test-retest intraclass correlation coefficient (ICC) of 0.84 [43], we decomposed a SD into a within-subject SD of 0.92 and a between-subject SD of 2.11.…”
Section: Sample Sizementioning
confidence: 99%
“…The difference between the mean SDQ hyperactivity/inattention ratings in MPH periods and placebo periods was used as a summary measure for the treatment effect in an individual subject. The estimated standard deviation (SD) of 2.3 points for single ratings was used based on a reported standard error for the parent-rated SDQ subscale [42]. Using a test-retest intraclass correlation coefficient (ICC) of 0.84 [43], we decomposed a SD into a within-subject SD of 0.92 and a between-subject SD of 2.11.…”
Section: Sample Sizementioning
confidence: 99%
“…Beim ersten Follow-up nach 10 Monaten waren die ADHS-Score-Effekte nur mehr halb so gut und nach 3 Jahren [162] bei leichter Verbesserung in allen Therapiegruppen nicht mehr signifikant unterschiedlich. Nach 8 Jahren [217] [209]. Daher und auch wegen der negativen Konsequenzen in der Transitionszeit [342] im Erwachsenenalter [259] sollte die Therapie bei persistierender Symptomatik auch über das Adoleszenzalter hinaus fortgesetzt werden.…”
Section: Fohlen Ein Weiterer Vorteil Ist Dassunclassified
“…2 Other studies found no association with QOL. 5,6 It is unclear how much of the negative outcomes associated with ADHD in children can be attributed to impairment resulting from the condition itself and how much is due to the labeling effect of the ADHD diagnosis. 7 H/I behaviors exist on a spectrum and correlate positively with impairment in domains, such as academic performance or socioemotional problems.…”
Section: Introductionmentioning
confidence: 99%